IMPROVING THE ACTIVITY AND ACHIEVEMENT OF MATHEMATICS LEARNING ON THE TOPIC OF ADDITION OF FRACTIONS BY USING VARIOUS METHODS OF GRADE VI STUDENTS OF MIS BANAU ACANGO - Husen, Hartati (Program Studi Pendidikan Profesi Guru Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry Banda Aceh, 2025)
Teaching is an activity to convey information in the form of knowledge given by teachers to students. Learning is a process of changing student behavior for knowledge, skills, values ​​and student learning achievements. However, there are several factors that affect student learning achievement, namely the teacher's teaching method, inadequate facilities. On the other hand, it is also influenced by the teacher's learning methods that are less varied, resulting in decreased student learning achievement and quickly bored. The purpose of this study is to describe student learning activity in teaching and learning, especially in Mathematics lessons using various methods and to describe student learning achievement in Mathematics lessons. This study uses several research procedures, namely action planning, action implementation, observation and evaluation and reflection. The results of this cycle of research showed satisfactory results for students and student learning achievement in Mathematics lessons increased, this can be seen from the student's score that reached the KKM.